Comparative efficacy of Amprolium, Garlic oil (Allium sativum) and Ginger oil (Zingiber officinale) against Coccidiosis in common quail (Coturnix coturnix) - ASGHAR, M.; DURRANI, U.F.; HUSSAIN, R.; MATLOOB, K.; MAHMOOD, A.K.; ANEES, M.; ONEEB, M. (Journal of the Hellenic Veterinary Medical Society, 2020)
In birds, Eimeria species are commonly reported coccidian parasites that cause anorexia, debilitation, bloody diarrhea, mortalities and economical losses. This study was conducted on 30 clinical cases of common quails presented at Pet Centre, University of Veterinary and Animal Sciences, Lahore, suffering from coccidiosis. The aim of this study was to evaluate in vivo comparative anti-coccidial efficacy of amprolium, garlic oil and ginger oil. Drinking water of affected birds was supplemented with amprolium (130 mg/1000 mL), garlic oil (150μL/100 mL) and ginger oil (150μL/100 mL) for 15 days and fecal sample screening for coccidia oocyst count was performed on days 0, 3, 5, 7, 11 and 15 using direct microscopy with fecal floatation method and McMaster chamber counting technique. Data was statistically analyzed which revealed that amprolium showed highest and rapid efficacy against coccidiosis with complete disappearance of oocysts and improved activity level with better health, increased feed intake and normal feces on day 11, followed by garlic oil that showed recovery from oocysts on day 15, whereas in ginger oil treated birds oocysts were present till the end of study. It was concluded that amprolium is highly effective against coccidiosis followed by garlic oil; on the other hand, ginger oil was not clinically effective for the treatment of coccidiosis in quails.